International symposium on exotic nuclei (World Scientific, 2005)
This volume comprises an important collection of papers dedicated to the problems of producing and investigating nuclei far from the line of stability. Together, they discuss the latest results on the production and study of the properties of the lightest to the heaviest nuclei as well as the current plans for future joint investigations in the field of exotic nuclei. The contributions from well-known experts in the field were presented at the International Symposium on Exotic Nuclei, jointly organized by four scientific centers where this field is actively pursued: Flerov Laboratory of Nuclear Reactions JINR (Dubna), RIKEN (Japan), GANIL (France), and GSI (Germany). Unique techniques for the synthesis and investigation of the properties of exotic nuclei are being developed together with the realization of large accelerator projects. The creation of these new radioactive ion beam factories requires substantial investment, and they can only be built with the support of international collaborations.